Development of a fast-acting nanosuspension nasal drop using a novel co-processed polymer for migraine relief - Shrisunder, Nikhil; Dhakad, Prashant Kumar; Gilhotra, Ritu (Creative Pharma Assent, 2025)
Background: Effective central nervous system (CNS) drug delivery remains challenging due to the blood-brain barrier. Nasal drug delivery offers a non-invasive alternative, ensuring rapid drug absorption and onset of action. Prochlorperazine Maleate, a drug for migraines, suffers from poor solubility, limiting its therapeutic potential. Methodology: A nanosuspension-based nasal drop was developed and optimized using high-pressure homogenization. A novel co-processed polymer enhances solubility and stability. Key formulation parameters, including particle size, zeta potential, and polymer concentration, were optimized using a central composite design. The optimized nanosuspension was characterized for its physicochemical properties, drug release, and stability. Results and Discussion: The optimized formulation (Batch F9) exhibited a particle size of 78.8 nm and a high drug release rate (93.87% in 8 hours). Stability studies confirmed no significant changes in drug content, pH, or osmolality over a three-month period. The nasal drop provided consistent dosing, with each actuation delivering a precise amount of drug content. In vitro drug release studies demonstrated a sustained release pattern, enabling prolonged migraine relief. Conclusion: The developed nanosuspension nasal drop presents a promising solution for CNS drug delivery, ensuring rapid and sustained therapeutic outcomes. This nanosuspension nasal drop achieved a 5.6-fold enhancement in solubility and demonstrated rapid onset within 10 minutes post-administration. Although promising, the study is limited to in vitro characterization; future research should explore in vivo efficacy and long-term safety.